Raising awareness on climate change through humor - Plaka, Valentina; Skanavis, Constantina; Topaltsis, L.; Τοπάλτσης, Λάμπρος; Σκαναβή, Κωνσταντίνα; Πλάκα, Βαλεντίνα (2024)
Environmental awareness, for issues like climate change, is on top of the list with the concerns, humanity is facing. We are being exposed to a gigantic number of environmental messages but still we haven’t reached the optimum level of environmental sensitivity. Most of the climate change awareness campaigns use fearful stimuli such as scary titles, and images of catastrophes and uncertain futures. That kind of campaigns create emotions like fear, anxiety and worry to the public. That’s an explanation why lots of people ignore climate change and deny its importance. According to various researches, humor can boost successfully educational and communication processes at stake. Participants being confronted with pleasant approaches have responded positively to the new information and their intention to retain longer their behavioral change has been recorded. Through a quality process, this study aims to study the importance of humor, and how it can be used in climate change awareness campaigns in a way that will influence public’s attitudes and behavior, so that a positive response will be created.